Determination of finasteride in the tablet form by liquid chromatography and its analytical method validation - CÜCÜ, AYŞEN (ELSEVIER SCIENCE BV, 2006)
A quantitative method for finasteride by liquid chromatography (LC) with UV detector, was validated for its new tablet form Dilaprost (R). Analysis was performed using Nova Pak C-18 column at 60 degrees C. Detection was carried out at a wavelength of 210 nm. The best separation for finasteride peak was achieved by isocratic elution with the mobile phase water/acetonitrile/tetrahydrofuran (80/10/10, v/v/v) and flow rate of 2 mL min(-1). The sample volume injected into liquid chromatography system was 15 mu L. Analytical method validation tests were performed. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: finasteride; Dilaprost (R); validation; RAT; 5-ALPHA-REDUCTASE